KONDISI HUTAN MANGROVE PADA AREAL PT. CITRA PUTERA KEBUN ASRI DI DESA SEBUHUR KABUPATEN TANAH LAUT - Ahmad Al Fajar; Setia Budi Peran; Abdi Fithria (Universitas Lambung Mangkurat, 2020)
Mangroves are forests that grow in brackish water and are affected by tides. This forest grows especially in places where there is puddling and accumulation of organic matter, either in bays that are protected from the onslaught of waves or around river mouths where water slows down and deposits the mud they carry from upstream. This study aims to determine the condition of flora in the area of mangrove forest diareal forest research PT. Citra Putra Kebun Asri which includes species diversity, species equality, and minimum livelihood values of each type. This research was carried out using a combination method between the path method and the plotted line method. In the studied mangrove forest area, two lanes with width 10 m and length of 100 m with distance of 20 m as the sample were measured, the path was made sub-plot, the type composition contained in this location amounted to 4 species of mangrove plant. The important value index (INP) of mangrove species at the growth rate of seedlings and poles is a good criterion because it has a value of 120-159%, while the growth rate of trees including criteria is quite good as it has a value of 120-179%, for fires, including the criteria that are not very good because at the growth rate of seedlings and stakes have a value of <40% and trees have a value <60%, All growth rates have a low index of species diversity value because it has a value <2, evenness index type at each growth rate has evenness of high species because it has a value> 0.6, minimum value of life in each species has a high value of> 0.1 so that the state of the plant in the location is still preserved sustainability.Keywords ; Vegetation analysis; Mangrove